Hubungan Durasi Olahraga dengan Durasi Penggunaan Internet dan Tingkat Keparahan Depresi pada Mahasiswa UIN Syarif Hidayatullah Jakarta - Sainsiana, Amalia; Arian, Andhika; Azzahra, Amadea; Asmar, Azmul; Hudiya, Aninditha; Hilmi, Haifa F; Nisa, Yunita F.; Noor, Isa M; Hendarmin, Laifa Annisa (Faculty of Medicine and Health Science, Universitas Islam Negeri Maulana Malik Ibrahim, 2021)
Background: Physical exercises provide benefits for everyone. Riset Kesehatan Dasar 2018 shows increased proportion of Indonesian who lack of exercise from 26.1% to 33.5%. Inadequate exercise can reduce productivity which can lead to excessive internet use and increasing the severity of depression. Objectives: To know the association between duration of exercise against duration of internet usage and the severity of depression amongst Syarif Hidayatullah State Islamic University Jakarta students. Methods: This is a non-experimental quantitative cross-sectional study on students of State Islamic University Jakarta using Patient Health Questionnaire-9 instrument, which has been validated by Confirmatory Factor Analysis method. Data were analysed by (1) descriptive statistics to obtain respondents general characteristics and the variables, (2) independent sample T-test to analyze the mean difference between the variables of men and women, (3) linear regression test to examine the relationship between the variables. Results: From 704 respondents, we found that 62.1% lacked of exercise, 57.8% using internet excessively, and 71.3% suffering moderate to severe depression. Furthermore, these results were common in women. There was significant negative association between duration of exercise (p-value = 0.000) and duration of internet usage, significant negative association between duration of exercise (p-value = 0.000) with the severity of depression, and significant positive association between duration of internet usage (p-value = 0.031) with the severity of depression. Conclusions: There is a significant association between duration of exercise with duration of internet usage and the severity of depression amongst Syarif Hidayatullah State Islamic University Jakarta students.Â Keyword : Exercise, Excessive Internet Use, Internet Addiction, Depression, Patient Health Questionnaire-9 (PHQ-9)